THE PROFILE OF SCHOOL LITERACY MOVEMENT AS AN EFFORT TO INCREASE READING MOTIVATION FOR PRIMARY SCHOOL STUDENTS IN KABUPATEN BONE - Irma Irma; Sitti Aida Azis; Sulfasyah Sulfasyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to describe the implementation of school literacy movement program (SLM) to increase students’ reading motivation at elementary school in cluster 1 of Kecamatan Tanete Riattang Barat, Kabupaten Bone. This study also aimed to reveal supporting and inhibiting factors in implementing SLM as well as the strategies developed by schools to overcome the inhibiting factors. This qualitative descriptive study utilized observations, interviews, and documentation to collect the data. The instruments of this study were observation sheets and interview guidelines. The subjects of this study were 15 respondents consisting of the principal, teachers, and students of grade VI and III. The results showed that the school implemented SLM program through habituation, development, and classroom learning activities. This program included the provision of facilities and infrastructure (such as libraries, reading corners, reading gardens, wall magazines, posters and slogans). In addition, SLM program was implemented because of the support from the school committee, school extra-curricular activities, and the provision of school funding allocations. Meanwhile, the inhibiting factors were the students' lack of understanding about the implementation of SLM, the inbalanced capacity of library capacity to the number of students, the insufficient book collection, and the minimum time available for reading activities. Thus, strategies to overcome these factors were providing students with an understanding of the application of SLM, expanding the reading garden, updating the book collection in the library, and making the maximum use of time during must-read hours.